Challenging Impunity: Colombia and Nicaragua's Intervention in the Israeli Genocide Case at the ICJ - Gunawan, Yordan; Prameswari, Elfa Rheanna; Himmaturrahmah, Himmaturrahmah (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
In 2023, Colombia and Nicaragua intervened in cases where Israel was accused of genocide. These interventions challenge the principle of impunity often enjoyed by powerful states. Colombia and Nicaragua have taken a stand against perceived injustices and sought to influence the course of the international legal process. This research used normative research methods, namely international law literature, legal documents, and previous ICJ decisions. This article analyzed the legal basis of the intervention and its impact on international law enforcement efforts related to genocide. This analysis is expected to contribute to the ongoing discussion in international law, particularly regarding state responsibility for the crime of genocide. This case challenges the practice of impunity in international law, particularly in relation to state actions deemed to violate human rights on a mass scale. This research also contributes to our understanding of the role of the ICJ in dealing with allegations of genocide, as well as the importance of small and medium-sized state interventions in fighting for international justice.